Employment and unemployment as indicators of labor market development in Krasnodar region - O. A. Martirosyan (Путеводитель предпринимателя, 2020)
In the current economic situation, the role of regions as subjects ofthe Federation in the development ofthe labor market is significantly increasing. Therefore, in order to solve the problem of employment and unemployment, it is necessary to build all the links in the employment management system in the region. The article deals with the main indicators of the labor market on the example ofthe Krasnodar region.